The effect of treatment by L-carnitine for infertile men on semen parameters - Abdul Rahman Jihad Manssor; Zaid Mohammed Mubarak Al–Mahdawi; Azzawi Mustafa Hadi (Tikrit Journal of Pure Science, 2019)
L-Carnitine (LC) is highly concentrated in the epididymis and plays a crucial role in sperm metabolism and maturation.